Micro-Fourier transform infrared spectroscopy of degradation-resistant organic microfossils; Influence of preservation environment and phylogeny - Versteegh, Gerard J. M.; Zonneveld, Karin A. F. (Frontiers in Marine Science, 2022)
To gain more insight into the effect of early diagenetic processes in different redox environments on the molecular characteristics of degradation resistant particulate organic matter, the molecular cyst wall characteristics of the closely related dinoflagellates Impagidinium aculeatum and I. patulum from oxic and anoxic sedimentary environments in the Madeira Abyssal Plain F-turbidite and in the surface sediments of the eastern Mediterranean Sea have been analysed with micro-FTIR spectroscopy. Both species have cysts that are representatives of particulate organic matter being extremely resistant against degradation in natural environments. Their walls primarily consist of a carbohydrate-based polymer. Spectral differences could not be observed between cysts from oxic and anoxic environments, neither from different areas nor from different geological times. However, we identify consistent compositional differences between both species. Compared to I. patulum, cyst walls of I. aculeatum contain more C-O probably of secondary alcohols that might imply a slightly higher resistance to decay of I. patulum. Comparison with cyst species that represent particular organic matter being extremely sensitive and slightly resistant against aerobic degradation in natural settings reveals that cysts walls of the most vulnerable species show C=N, N-H, N-O, C-N bending/stretching, as well as the presence of C=O and C-O bounds. Cyst species that are somewhat less sensitive have a strong indication of the presence of nitrogen in their macromolecules. More resistant species lack nitrogen whereas the most resistant cyst species I. aculeatum and I. patulum show low amounts of C=O.